2021
DOI: 10.3389/fgene.2021.705019
|View full text |Cite
|
Sign up to set email alerts
|

Hologene 5: A Phase II/III Clinical Trial of Combined Cell and Gene Therapy of Junctional Epidermolysis Bullosa

Abstract: Epidermolysis bullosa (EB) is a group of devastating genetic diseases characterized by skin and mucosal fragility and formation of blisters, which develop either spontaneously or in response to minor mechanical trauma. There is no definitive therapy for any form of EB. Intermediate junctional EB (JEB) caused by mutations in the gene LAMB3 has been the first genetic skin disease successfully tackled by ex vivo gene therapy. Here, we present a multicenter, open-label, uncontrolled phase II/III study that aims at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In each case, subconfluent keratinocyte cultures were monitored for holoclone-forming stem cells [52], providing an indirect estimate of EpiSCtargeting efficiency, and therefore, graft durability [33][34][35]. Data from these trials demonstrated that only a small population of holoclone-forming stem cells corresponding to approximately 5% of the total grafted cells were responsible for the long-term maintenance of a functioning transgenic epidermis [50]. This equated to the transplantation of approximately 1.8 × 10 3 EpiSCs per cm 2 to regenerate and maintain nearly the entire epidermis of the severely affected boy [33].…”
Section: Genetically Modified Ceasmentioning
confidence: 99%
See 4 more Smart Citations
“…In each case, subconfluent keratinocyte cultures were monitored for holoclone-forming stem cells [52], providing an indirect estimate of EpiSCtargeting efficiency, and therefore, graft durability [33][34][35]. Data from these trials demonstrated that only a small population of holoclone-forming stem cells corresponding to approximately 5% of the total grafted cells were responsible for the long-term maintenance of a functioning transgenic epidermis [50]. This equated to the transplantation of approximately 1.8 × 10 3 EpiSCs per cm 2 to regenerate and maintain nearly the entire epidermis of the severely affected boy [33].…”
Section: Genetically Modified Ceasmentioning
confidence: 99%
“…It is possible that resident C7-mutant keratinocytes from the wound edges or epidermal stem cell reservoirs colonised the grafted wound bed and outcompeted the grafted revertant cells RDEB [ 42 ] Case report 1 Keratinocytes from genetically revertant skin carrying two COL7A1 gene reversions cultured on a feeder layer of murine fibroblasts into keratinocyte sheets 16 years Mechanical displacement an issue for some grafts; however, the grafted site on the right knee remained closed for 16 years [ 48 ] [ 48 ] Investigator-initiated trial 3 Keratinocytes from genetically revertant skin carrying COL7A1 gene reversions cultured on a feeder layer of murine fibroblasts into keratinocyte sheets 76 weeks Eight refractory ulcers treated on each of three patients. 100% of grafts fully epithelialised for two patients and 52.6% for the third, achieving the trial’s primary endpoint of >50% Gene therapy JEB [ 35 , 49 , 50 ] Phase I/II trial 1 Genetically corrected keratinocyte sheets generated on a feeder layer of murine fibroblasts. For genetic modification, LAMB3 -deficient keratinocytes were grown with an amphotrophic retroviral packaging cell line expressing wild type full-length LAMB3 cDNA controlled under the MLV LTR within an MFG retroviral backbone 15 years Complete epidermal adhesion in the absence of blistering, inflammation or infection.…”
Section: Tesss For Ebmentioning
confidence: 99%
See 3 more Smart Citations